The Impact of Digital Finance on Corporate Technological Innovation: Evidence from Chinese A-Share Listed Companies - Yang, Nana; Nunthasen, Ke; Nunthasen, Waraporn; Sinnarong, Nirote (Rajapark Journal, 2024)
Digital finance, leveraging advanced digital technologies such as big data and artificial intelligence, profoundly influences the process of corporate technological innovation and significantly impacts the quality of economic development. This paper examines the impact and mechanism of digital finance on corporate technological innovation by matching the Peking University Digital Inclusive Finance Index (2011-2022) provincial data with data from Chinese A-share listed companies. Using bidirectional fixed effects models and mediation effect models for empirical analysis, the study finds that digital finance significantly promotes corporate technological innovation, and this conclusion remains robust after robustness tests. Digital finance enhances technological innovation by alleviating financing constraints, with financing constraints mediating this process. The impact of digital finance on technological innovation varies by scale and industry, with its effect being more pronounced for small and medium-sized enterprises and high-tech firms. This research contributes to providing more efficient financial support for corporate technological innovation through digital finance. It offers new insights for optimizing the development of digital finance and formulating targeted policies for technological innovation.